Provisional Agenda for the Twenty-Third Meeting of the International Monetary and Financial Committee. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
A joint meeting of IMFC and G-20 Members will be held on Friday, April 15 on The Governance of Multilateral Surveillance from 7:00 pagesm. until 8:30 pagesm. in HQ1 Meeting Halls A and B.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: HQ1; IMF Governors Photograph; Meeting Hall; PP